Postoperative analgesic effects of laserpuncture and meloxicamin bitches submitted to ovariohysterectomy - Tomacheuski, Rubia M. [UNESP]; Taffarel, Marilda O.; Cardoso, Guilherme S.; Derussi, Ana A.P.; Ferrante, Marcos; Volpato, Rodrigo [UNESP]; Luna, Stelio P.L. [UNESP] (MDPI, 2020)
Background: This prospective, randomised and blind study investigated the efficacy of laserpuncture for postoperative pain management in dogs. Method: Sixteen bitches were sedated with acepromazine and randomly treated before ovariohysterectomy with meloxicam 0.2 mg·kg-1 intramuscular or laserpuncture (wavelength 904 mm, frequency 124 Hz, potency 10 Joules, 100 s in each acupoint). Anaesthesia was performed with propofol, isoflurane/O2, and fentanyl. The Glasgow Composite Measure Pain Scale (GCMPS) and Dynamic Interactive Visual Analog Scale (DIVAS) were used to evaluate postoperative pain before and for 24 h after surgery. Morphine was administrated as rescue analgesia when pain scores were ≥3.33 (GCMPS). Differences between treatments, time points, and amount of rescue analgesia between groups were investigated by the Mann-Whitney test and the area under the curve (AUC) for GCMPS, Friedman, and Chi-squared tests, respectively (p < 0.05). Results: Dogs treated with laserpuncture presented lower GCMPS AUC for 24 h and lower GCMPS scores at 2 and 4 h postoperatively (p = 0.04). Three dogs treated with meloxicam required postoperatively rescue analgesia against none treated with laserpuncture. Conclusions: In this preliminary study, laserpuncture mitigated postoperative pain in dogs following ovariohysterectomy, and the technique is a promising adjunct to perioperative pain management in dogs undergoing soft tissue surgery.
Keywords: Acupuncture; Analgesia; Dogs; Low-level laser therapy; Pain